2007
DOI: 10.1038/sj.cdd.4402246
|View full text |Cite
|
Sign up to set email alerts
|

Tissue inhibitor of metalloproteinases-3 facilitates Fas-mediated neuronal cell death following mild ischemia

Abstract: Tissue inhibitor of metalloproteinase-3 (TIMP-3) is a natural inhibitor of metalloproteinases involved in matrix degradation and ectodomain shedding of many cell-surface proteins, including death receptors and/or their ligands. In the present study, we examined the role of TIMP-3 in Fas-mediated neuronal cell death following cerebral ischemia, using both gene deletion and pharmacological approaches. In culture, exposure of primary cortical neurons to 2 h of oxygen-glucose deprivation (OGD) resulted in delayed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 39 publications
4
56
1
Order By: Relevance
“…cellular matrix providing strength to the articular is the type II collagen (26). The degradation of type II collagen is caused by MMP-13, however, its activity is suppressed by TIMP-1 (27,28). Our current study revealed that ginsenoside-Rg5 treatment for one month significantly increased the expression of TIMP-1.…”
Section: Discussionsupporting
confidence: 49%
“…cellular matrix providing strength to the articular is the type II collagen (26). The degradation of type II collagen is caused by MMP-13, however, its activity is suppressed by TIMP-1 (27,28). Our current study revealed that ginsenoside-Rg5 treatment for one month significantly increased the expression of TIMP-1.…”
Section: Discussionsupporting
confidence: 49%
“…Our results provide insight into EGFR activation and ERK1/2 signal transduction in a TIMP3-deficient state, which commits hepatocytes to survival following Fas-mediated toxicity. In support of this interpretation, the protective role of the EGFR pathway is demonstrated in models of stress induced by UV and ROS (10,63), and a proapoptotic role of TIMP3 in Fas-mediated apoptosis has been suggested in neuronal and synovial fibroblast models in vitro (64,65). Our finding that dampened TNFR1 activation coupled with enhanced EGFR signaling is protective against acute hepatic failure is consistent with observations that individually, ablating JNK signaling or elevating EGFR activation can protect, at least in part, against receptor-mediated apoptosis (7,9).…”
Section: Discussionmentioning
confidence: 80%
“…Tissue inhibitor of metalloproteinase-3 also has been associated with neuronal apoptosis after ischemia (Wallace et al, 2002). Recently, TIMP-3 gene deletion was shown to prevent Fas-mediated cell death in focal ischemia (Wetzel et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Matrix metalloproteinases and TIMP-3 have been associated with neuronal apoptosis in cerebral ischemia (Wallace et al, 2002;Copin et al, 2005;Wetzel et al, 2007). We evaluated DNA fragmentation by TUNEL staining and cleaved caspase-3 expression in the caudate putamen and the cortex at 24 h after ischemia.…”
Section: Neuronal Apoptosis and Cleaved Caspase-3mentioning
confidence: 99%